2009
DOI: 10.1002/smll.200801179
|View full text |Cite
|
Sign up to set email alerts
|

3D Metallic Nanostructure Fabrication by Surfactant‐Assisted Multiphoton‐Induced Reduction

Abstract: communications Figure 6. a) SEM image of the free-standing silver pillar on the cover slip, made by using a laser power of 1.14 mW and a linear scanning speed of 3 mm s À1 , taken at an observation angle of 45 8. The inset is a close-up view of the silver pillar parallel to the substrate, which demonstrates the linewidth of the smallest portion of the silver pillar as 180 nm. b) SEM image of silver pyramids, fabricated with a laser power of 1.3 mW and scanning speed of 2.5 mm s À1 , taken at an observation ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
212
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(216 citation statements)
references
References 28 publications
(30 reference statements)
2
212
1
1
Order By: Relevance
“…Many micro/nano fabrication techniques featuring 3D structures that could be applied to photonic and MMs have been developed in recent years. These techniques include layer-by-layer stacking 3,14,15 , structural rolling 16,17 , shadow evaporation 18 , multilayer electroplating 19 , membrane projection lithography 20,21 , stress-driven assembly 22 , direct laser writing 8,[23][24][25][26][27][28] , and ion-beam irradiation [29][30][31] . However, effective fabrication of nanoscale 3D plasmonic structures that can be spatially oriented with a hierarchical geometry remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Many micro/nano fabrication techniques featuring 3D structures that could be applied to photonic and MMs have been developed in recent years. These techniques include layer-by-layer stacking 3,14,15 , structural rolling 16,17 , shadow evaporation 18 , multilayer electroplating 19 , membrane projection lithography 20,21 , stress-driven assembly 22 , direct laser writing 8,[23][24][25][26][27][28] , and ion-beam irradiation [29][30][31] . However, effective fabrication of nanoscale 3D plasmonic structures that can be spatially oriented with a hierarchical geometry remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] The method described here yields submicrometer silver structures that do not need to be self-supported because they are embedded inside a matrix. A doped polymer matrix is prepared using a mixture of silver nitrate (AgNO 3 ), polyvinylpyrrolidone (PVP) and water (H 2 O).…”
mentioning
confidence: 99%
“…High resolution SEMs (Figure 2) show that the metallic patterns are comprised of small metallic granules, indicating that the rate of photoreduction within the focal volume is limited by the diffusion of metallic precursors. [32][33][34] SEM cross-sectional analysis of an exemplary Pd structure revealed that the granular surface, in large part, is continuous throughout the structure interior down to the glass/metal interface at which point the structure appears solidified, indicating thermal melting/annealing at the interface-a consequence of heating via light absorption by the metallic pads. We estimated the steady state temperature rise (ΔΤ) at the laser focal point of the glass/metal interface using the solution for the low frequency limit (essentially CW) of the laser modulation: 35…”
Section: Supporting Information Placeholdermentioning
confidence: 99%